Gaya Bahasa Satire Dalam Konten Ormas Pada Kanal YouTube Deddy Corbuzier - Insani, A. Nurul; Mayong, Mayong; Fitri, Sakinah (Fakultas Teknik Universitas Negeri Makassar, 2024)
The purpose of this study is to describe the types of satirical language styles spoken by guest stars in Ormascontent on Deddy Corbuzier's YouTube channel. The research method applied in this study is a qualitative approach. In this study, the data collected includes 4 videos of Ormascontent published on Deddy Corbuzier's YouTube channel in the August 2023 edition. Each video has a duration of about 50 minutes. Furthermore, the videos were analysed to determine the type of satirical language style. The results showed that there were 28 types of satire sentences found, consisting of 21 horatian type satire, then 7 juvenalian type satire. Of the 28 satire styles found, the meanings of the satire styles provide an in-depth understanding of how satire is used to influence opinions and views among YouTube viewers.